Advancing trauma informed practices in schools using the Consolidated Framework for Implementation Research - Mullin, Alice C.; Sharkey, Jill D.; Barnett, Miya (Frontiers in Education, 2024)
As the world becomes more aware of the prevalence and consequences of trauma for young people, the education sector is increasingly responsible for supporting students emotionally and academically. School-based mental health supports for students who have experienced trauma are crucial, as schools are often the only access point for intervention for many children and families. Given that over two-thirds of children in the U.S. will experience a traumatic event by age 16, it is imperative to better understand the mechanisms of implementing mental health support in schools. Despite the increasing need for trauma-informed practices in schools (TIPS), schools often struggle to provide them due to a myriad of barriers. More research is needed to understand how to implement and sustain TIPS. Researchers have begun exploring these questions, but there is still a shortage of research about how to best implement TIPS. We argue that the Consolidated Framework for Implementation Research (CFIR) is useful for organizing and advancing the implementation of TIPS. By consolidating findings from existing scholarship on TIPS, we identify themes and future directions within the CFIR framework. Based on our review, we also provide practical suggestions for schools seeking to implement TIPS.